ChemInform Abstract: Dual Catalytic Activity of Palladium Doped with a Rhodium Complex in a One‐Pot, Four Step Process. Issue 46 (November 2015) - Shapiro, Leora; Driess, Matthias; Avnir, David
Abstract The H2 pressure is critical for the reaction outcome: lower pressure lowers the conversion, higher pressure favours ethylbenzene as final product.